Elimination of Mycoplasma Contamination from Infected Human Hepatocyte C3A Cells by Intraperitoneal Injection in BALB/c Mice - Weng, Jun; Li, Yang; Cai, Lei; Li, Ting; Peng, Gongze; Fu, Chaoyi; Han, Xu; Li, Haiyan; Jiang, Zesheng; Zhang, Zhi; Du, Jiang; Peng, Qing; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Abstract Background/Aims: The use of antibiotics to eliminate Mycoplasma contamination has some serious limitations. Mycoplasma contamination can be eliminated by intraperitoneal injection of BALB/c mice with contaminated cells combined with screening monoclonal cells. However, in vivo passage in mice after injection with contaminated cells requires a long duration (20-54 days). Furthermore, it is important to monitor for cross-contamination of mouse and human cells, xenotropic murine leukemia virus-related virus (XMRV) infection, and altered cell function after the in vivo treatment. The present study aimed to validate a reliable and simplified method to eliminate mycoplasma contamination from human hepatocytes. BALB/c mice were injected with paraffin oil prior to injection with cells, in order to shorten duration of intraperitoneal passage. Cross-contamination of mouse and human cells, XMRV infection and cell function-related genes and proteins were also evaluated.Methods: PCR and DNA sequencing were used to confirm Mycoplasma hyorhinis (M. hyorhinis) contamination in human hepatocyte C3A cells. Five BALB/c mice were intraperitoneally injected with 0.5 ml paraffin oil one week before injection of the cells. The mice were then intraperitoneally injected with C3A hepatocytes (5.0×106/ml) contaminated with M. hyorhinis (6.2±2.2×108 CFU/ml). Ascites were collected for monoclonal cell screening on the 14th day after injection of contaminated cells. Elimination of mycoplasma from cells was determined by PCR and Transmission Electron Microscopy (TEM). Human–mouse cell and XMRV contamination were also detected by PCR. Quantitative reverse transcription PCR and western blotting were used to compare the expression of genes and proteins among treated cells, nontreated infected cells, and uninfected cells. Results: Fourteen days after injection with cells, 4 of the 5 mice had ascites. Hepatocyte colonies extracted from the ascites of 4 mice were all mycoplasma-free. There was no cell cross-contamination or XMRV infection in treated cell cultures. Elimination of Mycoplasma resulted in partial or complete recovery in the expression of ALB, TF, and CYP3A4 genes as well as proteins. Proliferation of the treated cells was not significantly affected by this management. Conclusion: The method of elimination of Mycoplasma contamination in this study was validated and reproducible. Success was achieved in four of five cases examined.